Evaluation of indigenous Azospirillum isolates for growth promotion in black pep- per (Piper nigrum L) rooted cuttings - V Srinivasan, KP Sangeeth, R Suseela Bhai, (Journal of Spices and Aromatic Crops, 2008)
The aim of the present work was to evaluate the inoculation effects of indigenous Azospirillumspp. selectively isolated from various black pepper growing locations of Kerala and Karnatakain enhancing the growth and nutrient uptake of black pepper cuttings. Azospirillum isolatesBPaz4 and BPaz9 recorded 67% more plant height in rooted cuttings than untreated cuttings.The nitrogen, phosphorus and potassium uptake and total dry weight was significantlysuperior in treated plants. Increase in the uptake of iron, manganese, zinc and copper wasfound in BPaz9 treatment. Colonization of rhizosphere soil and nonrhizosphere by theseisolates was found to be high. The N2-fixation capacity of the isolates BPaz4 and BPaz9showed 8.68 and 8.52 mg g-1 malate. Thus the application of these inoculants viz. BPaz4 andBPaz9 is suggested for the ecofriendly production of rooted cuttings of black pepper.